A Variant of the RSA Cryptosystem with Smaller Keys (Dhaka University Journal of Science, 2022)
In this paper we introduce an efficient variant of the RSA cryptosystem which will need lesser memory for key storage which is lessen the computational cost. Introduction of the RSA cryptosystem by Rivest, Shamir, and Adleman in 1978 was a revolutionary step in cryptography. The regular RSA system needs huge cost for decryption due to large size of the private decryption key. The proposed variant will be a solution to this conundrum.Dhaka Univ. J. Sci. 70(2): 15-17, 2022 (July)